2007
DOI: 10.3346/jkms.2007.22.3.442
|View full text |Cite
|
Sign up to set email alerts
|

Vagus Nerve Stimulation in Intractable Childhood Epilepsy: a Korean Multicenter Experience

Abstract: We evaluated the long-term outcome of vagus nerve stimulation (VNS) in 28 children with refractory epilepsy. Of these 28 children, 15 (53.6%) showed a >50% reduction in seizure frequency and 9 (32.1%) had a >75% reduction. When we compared seizure reduction rates according to seizure types (generalized vs. partial) and etiologies (symptomatic vs. cryptogenic), we found no significant differences. In addition, there was no correlation between the length of the stimulation period and treatment effect. The seizur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
22
1
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 17 publications
4
22
1
2
Order By: Relevance
“…Our findings suggest, however, that VNS is an effective treatment modality regardless of the type of seizure, semiology, type of previous epilepsy surgery, or etiology. You et al showed that VNS tended to be better tolerated and more effective in younger patients 13) . They also found that VNS resulted in a >50% reduction in seizure frequency in 53.6% of the children in their study and a >75% decrease in seizure frequency 6 months after VNS implantation 13) .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings suggest, however, that VNS is an effective treatment modality regardless of the type of seizure, semiology, type of previous epilepsy surgery, or etiology. You et al showed that VNS tended to be better tolerated and more effective in younger patients 13) . They also found that VNS resulted in a >50% reduction in seizure frequency in 53.6% of the children in their study and a >75% decrease in seizure frequency 6 months after VNS implantation 13) .…”
mentioning
confidence: 99%
“…You et al showed that VNS tended to be better tolerated and more effective in younger patients 13) . They also found that VNS resulted in a >50% reduction in seizure frequency in 53.6% of the children in their study and a >75% decrease in seizure frequency 6 months after VNS implantation 13) . Our study shows that VNS implantation is also effective in adult patients.…”
mentioning
confidence: 99%
“…In general, VNS improved different HRQOL domains in children and adolescents, mainly cognitive, psychological, and social (You et al, 2007;Sherman et al, 2008). However, there was no statistical difference between those children with and without VNS (You et al, 2007).…”
Section: Impacts Of Vagus Nerve Stimulation On Hrqolmentioning
confidence: 92%
“…Three follow-up studies evaluated HRQOL in children and adolescents with implemented vagus nerve stimulation (VNS) (You et al, 2007;Sherman et al, 2008;Mikati et al, 2009). In general, VNS improved different HRQOL domains in children and adolescents, mainly cognitive, psychological, and social (You et al, 2007;Sherman et al, 2008).…”
Section: Impacts Of Vagus Nerve Stimulation On Hrqolmentioning
confidence: 99%
“…In evaluating the effects vagal nerve stimulators have on patients who receive it to reduce seizure frequency, numerous investigators have coincidentally noticed a benefit on cognition [175]. In a study of ten epileptic participants implanted with vagus nerve stimulators, 2 min of stimulation at 0.50 mA 30 s after reading text was found to enhance subsequent word recognition [26].…”
Section: Subcortical and Peripheral Stimulationmentioning
confidence: 99%